The research advances in Kirsten rat sarcoma viral oncogene homolog (KRAS)-related cancer during 2013 to 2022: a scientometric analysis - Huang, Yujie; Zheng, Daitian; Zhou, Zhongming; Wang, Haiting; Li, Yanpo; Zheng, Huihui; Tan, Jianhui; Wu, Jingyao; Yang, Qiuping; Tian, Huiting; Lin, Liuming; Li, Zhiyang; et al. (Frontiers in Oncology, 2024)
Introduction: Cancer represents a significant global public health concern. In recent years, the incidence of cancer has been on the rise worldwide due to various factors, including diet, environment, and an aging population. Simultaneously, advancements in tumor molecular biology and genomics have led to a shift from systemic chemotherapy focused on disease sites and morphopathology towards precise targeted therapy for driver gene mutations. Therefore, we propose a comprehensive review aimed at exploring the research hotspots and directions in the field of Kirsten rat sarcoma viral oncogene homolog (KRAS)-mutant cancers over the past decade, providing valuable insights for cancer treatment strategies. Specifically, we aim to present an intellectual landscape using data obtained from the Web of Science (WoS) regarding KRAS mutation.Methods: Bibliometrix, VOSviewer, CiteSpace, and HistCite were employed to conduct scientometric analyses on national publications, influential authors, highly cited articles, frequent keywords, etc.Results: A total of 16,609 publications met the screening criteria and exhibited a consistent annual growth trend overall. Among 102 countries/regions, the United States occupied the vast majority share of the published volume. The journal Oncotarget had the highest circulation among all scientific publications. Moreover, the most seminal articles in this field primarily focus on biology and targeted therapies, with overcoming drug resistance being identified as a future research direction.The findings of the thematic analysis indicate that KRAS mutation in lung cancer, the prognosis following B-Raf proto-oncogene, serine/threonine kinase (BRAF) or rat sarcoma (RAS) mutations, and anti-epidermal growth factor receptor (EGFR)-related lung cancer are the significant hotspots in the given field. Considering the significant advancements made in direct targeting drugs like sotorasib, it is anticipated that interest in cancers associated with KRAS mutations will remain steadfast.